An operationalizing model for measuring urban resilience on land expansion. (August 2020) - Du, Mengbing; Zhang, Xiaoling; Wang, Yuhua; Tao, Li; Li, Heng
Abstract: Urban resilience is increasingly considered a useful approach to accommodate uncertainties. As an important material basis of the urban system, the land is one of the most promising intermediaries to observe urban resilience and is useful to shape resilience potential through land use management. However, current research into the quantitative assessment of urban resilience on land is underexplored, leaving it largely unpracticed in contemporary planning and policy discourse. Here, we introduce an operational model for understanding city-level resilience on land expansion that integrates economic, social and environmental dimensions of ecosystems. Using multi-source data and employing spatial analysis methods, urban resilience is assessed from 1995 to 2015 in Tianjin, China as an illustration following the phases of the operational model. The results indicate that land expansion has a great influence on urban resilience, given economic resilience increases but simultaneous social and environmental resilience decrease. The findings suggest (i) urban resilience should be incorporated into the planning process that helps to balance the multiple tradeoffs involved; (ii) land use regulations are necessary to manage land by controlling the quantity and quality of land uses; (iii) local governments should be involved to make tailor-made strategies to enhance a concerted action of successful practice. Highlights: Provide an analytical framework for understanding city-level resilience no land expansion. Recognized multiple tradeoffs in land expansion and suggest urban resilience helps to balance these tradeoffs. It is necessary to use land use regulation as intervention for achieving urban resilence. Propose local governments be involved to enhance a concerted action of successful practice.